Investment expensing and progressivity in flat-tax reforms - Javier Díaz-Giménez; Josep Pijoan-Mas (SERIEs - Journal of the Spanish Economic Association, 2019)
In this article we quantify the aggregate, distributional and welfare consequences of investment expensing and progressivity in Hall and Rabushka type of flat-tax reforms of the US economy. To do so we use a heterogeneous households model featuring both life cycle and dynastic elements as well as nonlinear wage dynamics. Our findings suggest that moving toward a progressive consumption-based flat-tax scheme could achieve the goals of raising government income, stimulating the economy, and providing a safety net for the households that have been hit the hardest by the recession. In particular, we find that investment expensing brings about sizeable output gains and a nontrivial increase in after-tax income inequality. However, it results in aggregate welfare gains in steady state because the large deduction in the labor income tax acts as a boon for the income poor, because the larger capital stock implies that workers earn higher wages, and because investment expensing allows households to abandon poverty faster. We also find that the progressivity of the reforms matters for welfare: economies with more progressive flat-tax schemes are better for the very poor and are ultimately preferred by a Benthamite social planner as they allow households to achieve better consumption smoothing and a better allocation of their work effort across time and states.
Keywords: D31; E62; H23; 330; Flat-tax reforms; Efficiency; Inequality; Earnings distribution; Income distribution; Wealth distribution